An Assessment of the One Lecture-One Test Learning Model by Journalism Teachers - Omojola, Oladokun (Covenant Journal of Communication, 2019)
This article analyzes transcripts from a knowledgeable group that discoursed at length the one lecture - one test (OLOT) learning model â€“ a system that requires students to write a short test for 10 to 20 minutes after every lecture, for a score that counts toward the overall grade.Â This model contrasts with the traditional system in higher institutions that set two or three tests and give one or a few assignments in a semester. Investigation of OLOT started with a one-year survey and three-year longitudinal assessment. It proceeds with this work and shows via a color graphic analysis that, though OLOT appears capable of promoting students’ attendance, concentration, interest, and participation during lectures, this may not necessarily translate to better grades. Data from the transcripts show, however, that, absence of better grades notwithstanding, the learning system should be given the benefit of the doubt given the significant showing of the four parameters.